A Feasibility Study on Powdered Coconut Juice - Go, Timothy T.; Ramiscal, Edgar S.; Turay, Dahlia U. (Diliman, Quezon City College of Engineering, 2005)
The feasibility of powdered coconut juice was evaluated in this study. Powdered coconut juice is a healthy juice drink that contains all of the nutrients and health benefits of fresh coconut juice. The product has a long shelf life and is made more accessible and easier to transport by turning the fresh coconut juice into powder form. This coconut-based product was developed by the Department of Science and Technology (DOST) and is expected to help increase the utilization of the country's abundant supply of coconuts. The health benefits that can be derived from continuous drinking of the product could result to improved health of lifestyle. The study is composed of five major parts, namely market, technical, organizational, financial and social studies. Extensive research from different government and private agencies, internet and several available publications was conducted to gather sufficient data for the different parts of the study. In the market study, the feasibility of introducing the product into the local market and the best marketing strategies to utilize was determined. Analysis on the potential demand for the product showed that the best target market for the product are the people in Classes A and B as they could afford to buy more expensive products and tend to be more health conscious compared to the others. The powdered coconut juice will be marketed not as an ordinary thirst-quenching juice drink but as a healthy juice drink that could cleanse the body and improve overall health if taken daily and continuously. From the market study, it was concluded that the product is very marketable and has a lot of potential for entering the global market as well. After establishing the marketability, the technical feasibility of the product was evaluated. The best operational process procedures, materials, equipment and facility design for the production of powdered coconut juice were determined by evaluating the different feasible alternatives. Costs, availability, capacity, efficiency and available technology were considered in the evaluation; The results showed that the project is technically feasible. By considering the results of the technical study and the different characteristics of the different forms of ownership, the type of organization best suited for the venture, sufficient stability for the company, and allows flexibility and simplicity in the management of the whole organization. In the financial study, the overall cost of undertaking the operations of producing and selling the powdered coconut juice was estimated. Cash flows, assets, liabilities and all financial information from the operations of the organization were presented and evaluated using different financial measures. From this phase, it was determined that an investment of P16 million is needed for the project. Lastly, the impact of the project to the economy and society was assessed by conducting a social profitability analysis. The different qualitative benefits and disbenefits from the project were identified. The results of the Net Present Value, Internal Rate of Return and Benefit-Cost Ratio that were used in evaluation showed that undertaking the venture is favorable as the benefits from the project greatly outweigh the costs from it.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Food Processing Division of the Industrial Technology Development Institute (ITDI); Coconut products; Coconut water; Participatory monitoring and evaluation (Project management)